THE UTILIZATION OF CHICKEN BONE FLOUR AS A SOURCE OF CALCIUM IN COOKIES MAKING - Melanie Cornelia; Dhanny Prasetya Gozali (Reaktor, 2018)
Chicken bone contained high calcium, but that utilization was very limited and mostly as a waste. Calcium was needed for humans, especially who were in period of growth. The purpose of this research was to utilize chicken bone flour as a source of calcium in cookies making. Cookies were food products that often consumed by people in Indonesia because easy to make and have a longer shelf life. The initial phase of this research was to find the best process of chicken bone flour from broiler chicken bone and kampong chicken bone as raw materials. The best chicken bone flour have high calcium content of 18061.12 mg/100 g, low fat content 13.79% and yield 34.63%. The formulation of cookies making were trial to add 0, 5, 10, 15, and 20% of chicken bone flour into cookies. From scoring and hedonic test by panelists, cookies were made with additional 5% of chicken bone flour was more preferable. So the best formulation was cookies which has calcium content 464.03 mg/100 g, 26.58% fat, and hardness 1372.03 g/cm2.  These cookies have characteristics and nutrients better than the cookies control. Keywords: cabinet drying; calcium; chicken bone; cookies; flour